1961
DOI: 10.1080/00022470.1961.10468041
|View full text |Cite
|
Sign up to set email alerts
|

TheEffectofTemperatureonPhotochemical Oxidant Productionin a Bench Scale Reaction System

Abstract: In the 10 or so years since Haagen-Smit 1 proposed the photochemical mechanism for ozone formation in the lower atmosphere considerable effort has been made to determine the exact nature of the "smog reaction." A great number of the variables affecting this reaction have been demon-* Presented at the 54th Annual Meeting of APCA,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1963
1963
1978
1978

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It remains to be shown, however, if the effect is due to chemistry and/or meteorology. Laboratory studies 14 have shown that O3 production is enhanced with increasing temperatures, but modeling studies 15 have shown no effect. In either case, however, part of the temperature relationship can be explained by comparing the temperature and O3 distributions within a high pressure system.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be shown, however, if the effect is due to chemistry and/or meteorology. Laboratory studies 14 have shown that O3 production is enhanced with increasing temperatures, but modeling studies 15 have shown no effect. In either case, however, part of the temperature relationship can be explained by comparing the temperature and O3 distributions within a high pressure system.…”
Section: Discussionmentioning
confidence: 99%
“…Those early studies stimulated investigations of light scattering and aerosol formation in a number of model systems. The following systems have been investigated under irradiation: (1) sulfur dioxide in air, (2) hydrocarbonsulfur dioxide in air, (3) hydrocarbonnitrogen dioxide, (4) hydrocarbonnitrogen dioxidesulfur dioxide, and ( 5 ) auto exhaust.…”
Section: Aerosolsmentioning
confidence: 99%
“…The primary photochemical process for (1) has been studied by Hall and B l a~e t , (~~) Holmes and Daniels, (51) If steady-state conditions are assumed for NO, and atomic oxygen and if it is assumed that (6), (71, and (8) have gone to completion, the steady state concentration for atomic oxygen is : Reactions (8) and (9) are unimportant. (62) KiZ @(NO,) -t K,I @z(O,) ( (NO) where the rate constants are as defined in Table 1.…”
mentioning
confidence: 99%
“…Temperatures of the irradiation chamber varied from 95 to 105 °F and of the dark chamber from 85 to 90 °F. Alley and Ripperton 19 have reported higher oxidant values at these higher irradiation temperatures.…”
Section: Fumigation Proceduresmentioning
confidence: 96%